Risk and relationship of eating disorders with body image, stress and self-esteem among university students - Shabadi, Nayanabai; Arora, Meghna; M., Renuka; Gopi, Arun; R., Narayanamurthy M. (International Journal Of Community Medicine And Public Health, 2021)
Background: The study was conducted to find the prevalence rates of eating disorders, body dissatisfaction, low self-esteem and levels of stress in the students of JSSAHER and to also find out the relationship between the same with eating disorders. Methods: A survey was conducted among 160 participants and they were asked to fill out questionnaires containing EAT-26, PSS-4, Rosenberg self-esteem scale and contour drawing scale which assesses risk of eating disorder, stress, self-esteem and Body image satisfaction respectively. The data was analyzed. Results: It was found that the 16.9% of the participants were prone to eating pathologies. Among 160 students 60% were not satisfied by their bodies, 37.5% reported high levels of stress and 20% had low self-esteem. A statistically significant association was found between eating disorders risk and body dissatisfaction whereas no significant association was found between stress and self-esteem with eating disorders in our study. Conclusions:This study showcases that eating disorders are an upcoming issue and that more research is required to find the etiological factors which lead and predispose people to eating disorders in India.